Offenders’ Narratives on Criminal Desistance While Serving a Prison Sentence - Redondo Illescas, Santiago (Victims & offenders, 2022)
This study analyzes the early desistance narratives of a sample of 44 male offenders, between 20 and 50 years old, incarcerated in Spain for serious crimes. In particular, two types of the inmates’ stories are evaluated: 1) their narratives of personal change toward a non-criminal life (identity change, perceived self-efficacy and willingness for desistance); 2) their perceptions on those transitional or facilitator factors for desistance available to them (new learning, support and social bonding). Participants’ accounts show how many subjects, despite being still in prison, claim to have experienced favorable changes and have different facilitating factors to abandon their previous criminal life. Despite this, such early narratives of withdrawal are not exempt from ambivalences and contradictions, both between subjects and within subjects. The process of desistance and their contradictions was interpreted, in accordance with the reviewed literature, as a long journey which is often traversed in a circular and zigzagging manner. Finally, it has been discussed how the correctional system should play a major role in facilitating the personal changes and the social support necessary for the ex-offenders’ journey to desistance to be successful.